Results of vertical figure-of-eight tension band suture for fingernail disruption with fractures of distal phalanx - Suneel Kumar; Faisal Akhlaq Ali Khan; Hyder Ali; Madiha Siddique; Roqayyah Munawer Khursheed; Mujtuba Pervez Khan (Journal of the Pakistan Medical Association, 2021)
Abstract Objective: Fingertip injuries are not uncommon variety in tertiary care hospital presented with variable gradation of damage. Still it has been treated by different techniques like removing nail plate, repairing nail bed, dermabond adhesive and k-wire fixation of fracture. Therefore this study was conducted to give painless and stable fingertips to the patients by means of vertical figure of eight tension sutures. Material and methods: A self-controlled study was carried out in Dow University of Health Science, Civil Hospital Karachi. Study comprised of seventy four participants aged above 10 up to 60 years, of either gender. Study took six months from May 2019 to October 2019. OpenEpi version 3.0 was used to calculate data. All candidates were approached by non-probability purposive sampling technique. Data was gathered by filing relative proforma and was analysed by using SPSS version 21.0. Results: All patients were surgically managed. Local anaesthesia was given to sixty five patients whereas nine were operated under general anaesthesia. During follow up period of three months patients were assessed clinically and with radiological films for finger stability and fracture healing. All patients at early visits had pain and discomfort on moving joints. Five patients (6.8%) had infection which was managed by wound care, antibiotics and recovered completely but no one had ischemic insult. Conclusion: It is a simple and amazing technique which can be done safely. It helps in proper healing of distal phalanx fractures and a non-deformed fingertip. Results of this study have been compared with other Continuous...